Cattle‐associated risk factors for human tuberculosis in rural livestock‐keeping communities, Uganda. (25th November 2018) - Meisner, Julianne; Curtis, Kellie; Graham, Thomas W.; Apamaku, Michael B.; Manhart, Lisa E.; Rabinowitz, Peter M.
Abstract: Tuberculosis (TB) is a leading infectious cause of human death worldwide. In cattle, TB infection results in productivity losses, trade barriers and zoonotic transmission via milk, meat or direct contact. We conducted a cross‐sectional study in rural communities in Uganda between 2014 and 2016 to evaluate the association between tuberculosis skin test (TST) positivity in humans and cattle‐associated risk factors: household herd positivity and raw milk consumption. Human and cattle TSTs were performed in communities followed by a survey of household practices. TST data were available on 493 humans, 184 (37.3%) with positive results, and 1, 441 cattle, 50 (3.5%) with positive results. We fit separate log binomial generalized estimating equation models for the herd positivity‐human TST positivity association, stratified on sex; and for the raw milk consumption‐human TST positivity association, stratified on frequency of milk consumption. Having at least one TST‐positive bovid in the household's herd was significantly associated with lower risk of TB among men (prevalence ratio [PR] 0.66, 95% CI 0.49, 0.87) but was not significantly associated with TB among women (PR 1.21, 95% CI 0.76, 1.95). This apparent protective effect was contrary to our a priori hypothesis of higher exposure effect among men, the primary caretakers of cattle. This finding may be the result of residual confounding by socioeconomic status; wealthier individuals may be less likely to be TB positive, but more likely to have TST‐positive herds by virtue of larger herd sizes, ability to purchase new and possibly infected stock, and propensity to keep more TB‐susceptible European breeds. For raw milk consumption, effect estimates were close to one and not statistically significant. Thus, in settings where bovine TB prevalence is low, such as Uganda, cattle‐associated zoonotic transmission may be rare, and cattle‐associated risk factors may not be important drivers of human TB burden.